Integrasi Pembelajaran Digital Dalam Pendidikan Vokasional Agribisnis: Tantangan Dan Peluang - Edi Sulaiman; Suci Amalia; Akmal Attamimi; Aan Budianto (Bulletin of Community Engagement, 2021)
This study explores the integration of digital learning in vocational agricultural education, focusing on its challenges and opportunities at SMK Pertanian Alam Nusantara in Central Lampung Regency, Indonesia. As the global education landscape undergoes digital transformation, vocational schools are expected to adapt to ensure that students acquire relevant competencies for the 21st century. This qualitative research employed descriptive methods through observations, interviews, and documentation to analyze the dynamics of digital learning implementation. The findings revealed several key challenges, including limited infrastructure, low digital literacy among teachers and students, and unstable internet connectivity. However, these obstacles were counterbalanced by significant opportunities such as increased student learning autonomy, the transformation of teacher roles into facilitators, and the development of virtual collaborations with industries. The integration of digital platforms also supported the contextualization of learning materials and the development of critical thinking and problem-solving skills among students. In conclusion, while challenges remain, digital learning integration in vocational agribusiness education offers strategic benefits for enhancing the quality and relevance of learning. It requires long-term commitment, strong policy support, and collaboration among schools, industries, and government to build a sustainable digital learning ecosystem